Admissions to Canadian Hospitals for Acute Asthma: A Prospective, Multicentre Study. Issue 1 (2010) - Rowe, Brian H; Villa-Roel, Cristina; Abu-Laban, Riyad B; Stenstrom, Rob; Mackey, Duncan; Stiell, Ian G; Campbell, Sam; Young, Bryan
Abstract : BACKGROUND: Asthma exacerbations constitute one of the most common causes of emergency department (ED) attendance in most developed countries. While severe asthma often requires hospitalization, variability in admission practices has been observed. OBJECTIVE: To describe the factors associated with admission to Canadian hospitals for acute asthma after ED treatment. METHODS: Subjects 18 to 55 years of age treated for acute asthma in 20 Canadian EDs prospectively underwent a structured ED interview (n=695) and telephone interview two weeks later. RESULTS: The median age of the patients was 30 years, and the majority were women (62.8%). The admission rate was 13.1% (95% CI 10.7% to 15.8%). Admitted patients were older, more often receiving oral or inhaled corticosteroids at presentation, and more frequently receiving systemic corticosteroids and magnesium sulphate in the ED. Similar proportions received beta-2 agonists and/or ipratropium bromide within 1 h of arrival. On multivariable analyses, factors associated with admission included age, previous admission in the past two years, more than eight beta-2 agonist puffs in the past 24 h, a Canadian Triage and Acuity Score of 1 to 2, a respiratory rate of greater than 22 breaths/min and an oxygen saturation of less than 95%. CONCLUSION: The admission rate for acute asthma from these Canadian EDs was lower than reported in other North American studies. The present study provides insight into practical factors associated with admission for acute asthma and highlights the importance of history and asthma severity markers on ED decision making. Further efforts to standardize ED management and expedite admission decision-making appear warranted.